Global consumption of protein and calories: Interrelation with the diet and products for elimination of deficiency - A. A. Stepanova; L. K. Asyakina (Пищевые системы, 2025)
Healthy nutrition with a balanced diet and sufficient caloric content facilitates longevity and control of non-communicable diseases. It also increases resistance to stress, pressures and unfavorable effects of the environment. The aim of the research was to analyze the dynamics of the global consumption of protein and calories and their interrelation with the diets of the population from various regions, as well as to assess food products that are able to make up for a deficiency in protein, dietary fiber and other nutrients. Analysis of data from the Rosstat and Food and Agriculture Organization of the United Nations showed that the lowest level of consumption of protein and calories was observed in Africa compared to world indices. This is conditioned by mainly plant-based diets. In Asia, indices of protein and calorie consumption are close to the world values. Diets include a significant amount of fish and seafood, plant-based foods and whole grain products. The highest indices were found in America, Oceania, Europe and Russia. Diets of their populations are more balanced; however, they include significant amounts of saturated fats and simple carbohydrates. Analysis of the data array containing information about 100 healthiest foods taken from Kaggle and processed in the program Power BI was able to reveal products that are most rich in protein, dietary fiber and vitamin C, as well as to detect the antioxidant index of products, their caloric content and geographical origin. It is nutrition that ensures the physical and mental activities of humans, their mood and quality of life. Therefore, by energy value and sets of products used in daily diets, nutrition should correspond to the age, gender, occupation, general health state of humans and the climate and geographical zones where they live.